Evaluation of Artesunate-mefloquine as a Novel Alternative Treatment for Schistosomiasis in African Children (SchistoSAM): protocol of a proof-of-concept, open-label, two-arm, individually-randomised controlled trial. Issue 6 (24th June 2021) - Roucher, Clémentine; Brosius, Isabel; Mbow, Moustapha; Faye, Babacar Thiendella; De Hondt, Annelies; Smekens, Bart; Arango, Diana; Burm, Christophe; Tsoumanis, Achilleas; Paredis, Linda; van Herrewege, Yven; Potters, Idzi; et al.
Abstract : Introduction: Alternative drugs and diagnostics are needed for the treatment and control of schistosomiasis. The exclusive use of praziquantel (PZQ) in mass drug administration programmes may result in the emergence of drug resistance. PZQ has little activity against Schistosoma larvae, thus reinfection remains a problem in high-risk communities. Furthermore, the insufficient sensitivity of conventional microscopy hinders therapeutic response assessment. Evaluation of artesunate-mefloquine (AM) as a Novel Alternative Treatment for Schistosomiasis in African Children (SchistoSAM) aims to evaluate the safety and efficacy of the antimalarial combination artesunate-mefloquine, re-purposed for the treatment of schistosomiasis, and to assess the performance of highly sensitive novel antigen-based and DNA-based assays as tools for monitoring treatment response. Methods and analysis: The SchistoSAM study is an open-label, two-arm, individually randomised controlled non-inferiority trial, with a follow-up of 48 weeks. Primary school-aged children from the Richard Toll district in northern Senegal, an area endemic for Schistosoma mansoni and Schistosoma haematobium, are allocated to the AM intervention arm (3-day courses at 6-week intervals) or the PZQ control arm (single dose of 40 mg/kg). The trial's primary endpoints are the efficacy (cure rate (CR), assessed by microscopy) and safety (frequency and pattern of drug-related adverse events) of one AM course versus PZQ at 4 weeks after treatment. Secondary endpoints include (1) cumulative CR, egg reduction rate and safety after each additional course of AM, and at weeks 24 and 48, (2) prevalence and severity of schistosomiasis-related morbidity and (3) malaria prevalence, incidence and morbidity, both after 24 and 48 weeks. CRs and intensity reduction rates are also assessed by antigen-based and DNA-based diagnostic assays, for which performance for treatment monitoring is evaluated. Ethics and dissemination: Ethics approval was obtained both in Belgium and Senegal. Oral assent from the children and signed informed consent from their legal representatives was obtained, prior to enrolment. The results will be disseminated in peer-reviewed journals and at international conferences. Trial registration number: NCT03893097 ; pre-results.